Potential Processing of Biogas Products for the Needs of Villagers in Jimbaran Village, Puspo District, Pasuruan Regency - Farrah, Amala Ikbar; Gunawan Prayitno; Alfisyah, Beta Dwiyanti; Arizkha, Yulia Faizatul; Nur, Zahara Azizah (Journal of Applied And Theoretical Social Sciences, 2021)
The rise follows the increase in population in energy consumption that causes a decrease in the supply of non-renewable energy in the world. With its wealth in natural resources, Indonesia is even predicted to experience a decline in oil supply as renewable energy within 15 years. Therefore, energy transformation needs to be done slowly. This research emphasizes renewable energy utilization projects with high potential that have not been optimized, one of which is through cow manure processing into biogas products. The purpose of the research in Jimbaran Village, Puspo Subdistrict, Pasuruan Regency is to further explore the plan of processing cow manure into Jimbaran Village's biogas products. The method used in research activities is the descriptive research method. Data collection is done online through virtual calls between researchers and the Jimbaran village apparatus, the Village Secretariat. The data obtained were analyzed with PRA (Participatory Rural Appraisal) and RRA (Rapid Rural Appraisal) data analysis techniques. Based on the survey results and data analysis, a biodigester procurement project plan was obtained as a form of a program developed in the study area to utilize cow manure as input for renewable energy processing. Through the biodigester procurement plan, it is expected that biogas products can provide fuel to rural communities with their farms' potential